2018
DOI: 10.1159/000486442
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Sample Adequacy in Liquid-Based Cytology after Ultrasonography-Guided Fine-Needle Aspiration of Thyroid Nodules: A Single-Center Study

Abstract: Objective: The factors that influence the acquisition of adequate samples during liquid-based cytology (LBC) remain unclear. This study aimed to identify factors that affect cytological adequacy in LBC after ultrasonography (US)-guided fine-needle aspiration (US-FNA) of thyroid nodules. Study Design: From January 2017 to May 2017, a single radiologist performed US-FNA to diagnose 112 thyroid nodules in 112 consecutive patients. Based on US findings after US-FNA, the size, location, position, composition, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…Nodule composition may also play a role in the number of passes performed. In contrast to other studies 7,8 that have shown FNAs of cystic nodules usually require more passes to meet the adequacy criteria, our study suggests that when a major component of the nodule is cystic, or has a cystic component, three passes are often all that is needed to meet adequacy requirements (Table 4). We speculate that although the overall cellularity in cystic nodules may be low, the presence of cystic features (ie, hemosiderin‐laden macrophages and cyst‐lining cells), in conjunction with unremarkable albeit scant follicular cells, can be a reassuring finding that may positively impact adequacy assessment.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Nodule composition may also play a role in the number of passes performed. In contrast to other studies 7,8 that have shown FNAs of cystic nodules usually require more passes to meet the adequacy criteria, our study suggests that when a major component of the nodule is cystic, or has a cystic component, three passes are often all that is needed to meet adequacy requirements (Table 4). We speculate that although the overall cellularity in cystic nodules may be low, the presence of cystic features (ie, hemosiderin‐laden macrophages and cyst‐lining cells), in conjunction with unremarkable albeit scant follicular cells, can be a reassuring finding that may positively impact adequacy assessment.…”
Section: Discussioncontrasting
confidence: 97%
“…There are few studies that have examined the effect of nodule size on the number of needle passes. Our study is in line with the study performed by Lee 8 and shows a similar effect of nodule size on specimen adequacy (Table 4). While the exact cause and effect relationship of these factors is currently not well understood, our speculation is that the larger nodules may have more hemorrhage or fibrosis requiring additional passes to meet adequacy criteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(11)(12)(13). The values of FNA and FNC with different needle gauges have been extensively investigated in the previous studies (14)(15)(16)(17). However, there are relatively less studies reporting the application of FNA in suspected cervical lymph nodes even this method has been recommended in ATA guideline (2).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck surgeons working at five other hospitals without a paper on CNB were contacted to obtain information on their use of CNB, and they confirmed that they rarely used CNB in clinical settings. Therefore, data from 14 papers [30,[32][33][34][35]41,46,[48][49][50]52,54,56,57] published by authors from eight hospitals favoring CNB were compared to data from 10 papers [25,28,29,37,38,43,45,47,53,60] published by authors from six hospitals that did not favor CNB to identify differences in the proportions of diagnoses according to the TBSRTC. Fig.…”
Section: Differences In the Proportions Of Diagnoses On Consecutive Fmentioning
confidence: 99%